2000
DOI: 10.1042/cs1000137
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration in peak systolic velocity is closely related to ischaemia during angioplasty: a vectorcardiographic and tissue Doppler imaging study

Abstract: We tested the hypothesis that the extent of signs of ischaemia detected by vectorcardiography (VCG) during elective coronary angioplasty (percutaneous transluminal coronary angioplasty; PTCA) is related to systolic and diastolic myocardial velocities, as determined by tissue Doppler echocardiography. A total of 15 patients undergoing PTCA (12 men/three women; age 61+/-9 years), without prior myocardial infarction and with an ejection fraction of >50%, were included. The balloon inflation was repeated three tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Alam et al (2000) studied patients following first myocardial infarction using myocardial velocity to quantify LV systolic and diastolic functions. Another study has shown that deterioration of peak systolic velocity accompanied ischaemia during angioplastic balloon inflation (Jensen et al, 2001). Another study has shown that deterioration of peak systolic velocity accompanied ischaemia during angioplastic balloon inflation (Jensen et al, 2001).…”
Section: Myocardial Velocity and Its Use For Quantification Of LV Funmentioning
confidence: 99%
See 1 more Smart Citation
“…Alam et al (2000) studied patients following first myocardial infarction using myocardial velocity to quantify LV systolic and diastolic functions. Another study has shown that deterioration of peak systolic velocity accompanied ischaemia during angioplastic balloon inflation (Jensen et al, 2001). Another study has shown that deterioration of peak systolic velocity accompanied ischaemia during angioplastic balloon inflation (Jensen et al, 2001).…”
Section: Myocardial Velocity and Its Use For Quantification Of LV Funmentioning
confidence: 99%
“…It is thus logical to presume that cardiac response to stress very much depends on the stress modality. Colour tissue Doppler information, TVI (Brodin et al, 1998), has recently been used to study systolic and diastolic functions in myocardial ischaemia (Alam et al, 2000;Jensen et al, 2001). In a recent meta-analysis, however, dipyridamole was found to have provided more 'interpretable'; results of wall motion score compared with exercise stress (de Albuquerque Fonseca & Picano, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The timescale of the findings was also validated in animal studies performed by Derumeaux et al. (1998) who showed induction of velocity disturbances already after 5 s. The response in humans to acute ischaemia was shown by Jensen et al. (2001) in a study where they measured basal anterior and septal myocardial velocities during PTCA procedures in the left anterior descending (LAD) coronary artery.…”
Section: Established Diagnostic Cardiac Entities Todaymentioning
confidence: 65%
“…The quantitative velocity response to ischaemia was early validated in experimental studies in animals against sonomicrometric crystals (Gorcsan et al, 1998). The timescale of the findings was also validated in animal studies performed by Derumeaux et al (1998) who showed induction of velocity disturbances already after 5 s. The response in humans to acute ischaemia was shown by Jensen et al (2001) in a study where they measured basal anterior and septal myocardial velocities during PTCA procedures in the left anterior descending (LAD) coronary artery. An induction of apical ischaemia induced systolic velocity changes even in the basal segments within 30 s of occlusion.…”
Section: Established Diagnostic Cardiac Entities Todaymentioning
confidence: 90%
“…The study of tissue velocities in the myocard using an apical window may seem narrow, but this is in fact frequently used for the investigation of myocardial performance [4][5][6], as well as derived variables calculated using data acquired this way [7]. Thus both corrected and non-corrected velocities have been used for calculating strain, as peak systolic strain is an easily calculated variable.…”
Section: Introductionmentioning
confidence: 99%